The cytosolic invertase NI6 affects vegetative growth, flowering, fruit set, and yield in tomato - Coluccio Leskow, Carla (2021)
Fil: Coluccio Leskow, Carla. Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto De Investigación Biotecnología (IB). Hurlingham, Buenos Aires, Argentina.